Uma análise comunicacional das redefinições na experiência de compra: o uso de dispositivos e o supermercado expandido - Rodrigues, Paula Izabela Nogueira Bartkiw (2017)
The research analyzes recent variations in the experience of everyday shopping in a supermarket due to the use of technologies. However, considering that understanding the past is fundamental to understanding the present (which in the case of this work involves the historical transformations related to the act of buying), we address variations in the process performed by the consumer with the use of technologies 'in duration' from the beginnings of retail (Juracy Parente) to hypermodernity (Gilles Lipovetsky). As of 2010, the popularization of the Internet and the use of information and communication technologies in commercial activities promoted new experiential adaptations related to consumption, defining a new communication configuration in the supermarket sector: there are cultural changes (Raymond Williams) that can be observed in the relationship, work and communication are structured (Manuel Castells). The complexity associated with such a reconfiguration justifies analyzing consumption actions going beyond of the simple exchange of commodities, but also including the attribution of meanings, as well as the establishment of relations and affections in the act of buying (Daniel Miller) which can occur at any time, place and time. This way, understand to what extent the supermarket redefines these relationships among consumer choices, taking into account tastes and relationships of affection, culture, identities, and the shopping experience. In this sense, the empirical material analyzes the digital purchase structure. For this purpose, direct interviews were conducted through a questionnaire structured with 18 questions with online consumers, participants and followers of the fan page of some of the supermarkets present in the digital social network Facebook. The analysis of the answers showed that what can be defined as an experience of purchase amplified by the use of mobile devices (such as notebooks, smartphones and tablets), a redefinition of the own culture in the age of mobility, which make the physical space of the supermarket an extension of home, work, leisure and the individual itself and which is addressed in the dissertation as constituting the 'expanded supermarket' of hypermodernity.